PENGARUH HARGA DAN KUALITAS MODUL TERHADAP KEPUTUSAN MENGIKUTI PELATIHAN DAN CITRA MEREK SEBAGAI VARIABEL INTERVENING PADA MENTARI TEACHERS ACADEMY JAKARTA - Kristianto, Andreas Kukuh; Fathorrahman, Fathorrahman; Pradiani, Theresia (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2024)
One of the reasons for the increase in the number of institutions offering teacher training is the increasing awareness among educators and instructors of the need to maintain and expand their competencies on an ongoing basis. With a vision and mission to become a teacher training center for Indonesian, English, Mathematics and Science subjects as well as general topics of pedagogical, social and character competencies for teacher professional development, Mentari Teachers Academy is a service unit that was founded in 2015 and offers training to educators and teachers. The aim of the research is to find out how the cost and quality of the module influence the decision of participants to take training and how it influences brand perception as an intervening variable for Mentari Teachers Academy training participants in 2024. Purposive sampling is the sampling strategy used, and the data analysis approach is path analysis with Sobel test using the SPSS 29 data processing program. The findings of this study show that brand image is positively and significantly influenced by the price and quality of the module. In addition, the choice to take training is positively and significantly influenced by cost, module quality and brand reputation. Module quality has a positive and significant influence on the decision to take training through brand image, but price apparently does not have a positive and significant influence on purchasing decisions through brand image. Keyword: Price, Mudule Quality, Brand Image, Decision to Participate in a Training